Establishing a nexus between executive functions and management efficacy of academic leaders - Bryan B. Gabatino; Bonimar T. Afalla (International Journal of Evaluation and Research in Education (IJERE), 2021)
Executive functions enable an individual to initiate and stop actions, track and modify behavior, and plan imminent behavior when faced with specific tasks and circumstances. This study, therefore, identified a connection between the executive functions and management efficacy of academic leaders of a State University in the Philippines. The Behavior Rating Inventory of Executive Function-Adult Version was used in a correlation analysis to gauge the executive functions of academic leaders and a researcher-made questionnaire was administered to determine their management efficacy. The study was conducted using t-scores, means, and Pearson r. The stronger the potential of academic leaders to carry out their management skills, the more their emotional regulation leans towards the borderline. As academic leaders' management skills become remarkable, the more they are predisposed to functioning on their own initiative and can control their actions in the light of the circumstances. Further, when academic leaders normally conduct change, self-monitoring, initiation, planning/organization, and task monitoring functions, they exemplify outstanding performance in their communication skills, adaptability, interpersonal relationships, and initiative, and imagination. But when their working memory, cognitive control, inhibition, and arrangement of materials is at the borderline, better interpersonal relationships, decision-making and judgment, and initiative and imagination are achieved.